“QUANDO VOCÊ TRANSICIONA, VOCÊ VIRA UMA BORBOLETA E SAI DO CASULO”: ITINERÁRIOS TERAPÊUTICOS DE HOMENS TRANS EM TRANSIÇÃO DE GÊNERO - Mattos, Mario Henrique de (2020)
This research aims to understand the therapeutic itineraries of trans men living in Guarapuava, a medium-sized municipality in the Paraná, understanding the itinerary as an analyzer of tensions produced in the relationship between this population and the health network. Besides understand the trajectories of this population in search of care with the health in the most diverse spaces, we also seek to understand their strategies and resources used to make possible bodily changes that make part of your gender transition. The work is constituted as a research qualitative, under the analytical-institutional perspective, carried out through of semi-structured interviews with four trans men who are in gender transition process. For the exposure of the results and analysis, analyzers were built, which gave rise to five lines of analysis. In the first line of analysis, the first experiences by trans men, ranging from self-recognition as a man trans, even the search for information about transsexuality through social networks, self-medication and the use of prostheses, such as binder and packer. The second line of analysis addresses the paths taken and the relationships established between trans men and health systems. Those paths are permeated by several barriers, such as the lack of knowledge of health professionals on policies aimed at serving people trans and the non-availability of services from the geographical point of view meet these needs. In the third line of analysis, stigma is analyzed as a crossing of the actions and services offered. Beyond of access to health services, stigma operates in the lives of these subjects in various contexts in which they are inserted, such as family, school and the work, insinuating themselves about their ways of existing. In this sense, it is evidence of the way in which the institutions and establishments that permeate the subjects expand or restrict their possibilities of existence. In the fourth line of analysis, the paper analyzes the search for recognition of trans men, through the use of their social name and body modification surgeries and the use of hormones. These instruments operate in the subjects' lives not only as health promoters, but also as also as mechanisms for control and maintenance of the current order. At fifth line of analysis, the issue of HIV / AIDS prevention is analyzed from from the interviewees' reports, highlighting the lack of visibility on this topic in social discussions, especially with regard to the creation of public prevention policies for this population. In this sense, the research brings the importance of the debate about transsexuality in the most varied contexts, in order to minimize the situations of vulnerability experienced by these subjects.